Insulin action on heart and skeletal muscle glucose uptake in weight lifters and endurance athletes - Takala, T. O.; Nuutila, P.; Knuuti, J.; Luotolahti, M.; Yki-Jarvinen, H. (American Journal of Physiology, Endocrinology and Metabolism, 1999)
There are no studies comparing myocardial metabolism between endurance- and resistance-trained athletes. We used 2-deoxy-2-[18F]fluoro-D-glucose and positron emission tomography combined with the euglycemic hyperinsulinemic clamp technique to compare the ability of insulin to stimulate myocardial, skeletal muscle, and whole body glucose uptake between weight lifters (n = 8), endurance athletes (n = 8), and sedentary men (n = 9). Maximal aerobic power (ml. kg- 1. min- 1) was higher in the endurance athletes (71 +/- 2, P < 0.001) than the weight lifters (42 +/- 2) and the sedentary men (42 +/- 2). Skeletal muscle glucose uptake (micromol. kg muscle- 1. min- 1) was enhanced in the endurance athletes (125 +/- 16, P < 0.01) but was similar in weight lifters (59 +/- 12) and sedentary (63 +/- 7) men. The rate of glucose uptake per unit mass of myocardium (micromol. kg- 1. min- 1) was similarly decreased in endurance athletes (544 +/- 50) and weight lifters (651 +/- 45) compared with sedentary men (1,041 +/- 78, P < 0.001 vs. endurance athletes and weight lifters). Both groups of athletes had increased left ventricular mass. Consequently, total left ventricular glucose uptake was comparable in all groups. These data demonstrate that aerobic but not resistance training is associated with enhanced insulin sensitivity in skeletal muscle. Despite this, cardiac changes are remarkably similar in weight lifters and endurance athletes and are characterized by an increase in left ventricular mass and diminished insulin-stimulated glucose uptake per heart mass.